Nocturnal Frontal Lobe Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The clinical and polysomnographic findings in 100 consecutive cases of nocturnal frontal lobe epilepsy (NFLE) were analysed in a study at the Neurological Institute, University of Bologna, Italy.